Avaliação do emprego da ultrafiltração em membrana na remoção de células de cianobactérias para águas de abastecimento - Alisson Braganca Silva (2008)
The aim of this research was to verify the cyanobacterial cells removal by means of ultrafiltration membrane technology in a pilot scale. This study took place in Pampulha Lake in Belo Horizonte, Minas Gerais, Brazil. The pilot plant has operated from April to August 2008. The operation of UF membrane pilot plant was monitored during 80 hours.Cyanobacterial blooms have become common at many water treatment plants around the world. Many problems in water treatment plants concerning cyanobacteria can be mentioned like: tastes and odors in the water; media filter clogging which increases backwashing frequency, and therefore increasing the operational costs. Finally these blooms may produce toxic compounds that could do harm for consumers.In this research the following parameters were analyzed such as pH, alkalinity, hardness, turbidity, true color, apparent color and counting of phytoplankton. It were detected Total coliforms and Escherichia coli in raw water and the permeate by Colilert Test kit. Cianobacterial toxin analysis was determined by ELISA method. The study pointed ultrafiltration membrane out was not able to remove hardness and alkalinity efficiently because this membrane can not reject ions like Ca, Mg. In the other hand, Escherichia coli was effectively removed during the test period. About apparent color, the medium UF membranes removal achieved over 90%. Nevertheless, the UF pilot plant could only remove true color by 35% because the UF membrane can not reject most of dissolved organic matter from raw water. The UF membrane achieved 5 log removal of Cylindrospermopsis raciborskii and Sphaerocavum brasiliense during each cyanobacterial blooms. Besides removing cells, the UF membrane pilot scale could remove microcystin efficiently at 68 F and 20 psi, nevertheless this one couldnt reject alkaloid toxins. Finally, this research concluded that UF membrane is able to remove cells of algae and cyanobacteria efficiently.